The impact of logistics performance index on port infrastructure quality: comparative study Tunisia Morocco - Ben Haj Ahmed, Rihab; Bouzir, Aida; Benhadj Mbarek, Mohamed Hédi; Benammou, Saloua (Archives of Transport, 2023)
This scientific article examines the relationship between logistics performance indices and port infrastructure quality in Tunisia and Morocco. The quality of port infrastructure (QPI) is an important component of the competitiveness port. It represents a driving force for the economic dynamics. This quality of port infrastructure is a complex subject on which a great deal of research has emerged in the last decade. The logistics performance index (LPI) serves as a crucial indicator to assess the efficiency and effectiveness of a country's logistics system. Accordingly, this paper aims to develop a model for assessing the quality of port infrastructure. The objective is to evaluate the development of port infrastructure to improve the competitiveness of port systems in two North African countries according to nine competi-tiveness criteria. The analysis involves statistical techniques such as regression modeling to establish relationships. The partial least squares (PLS) regression method is adopted to obtain a reliable estimate, using nine explanatory variables :(performance indicators) (overall, the frequency with which shipments reach their recipient within the set deadlines, The efficiency of customs clearance process, ease of arranging competitively priced shipments, Lead time to import, Lead time to export, competence and quality of logistics services, Liner Shipping Connectivity Index, Container port traffic) and quality of the port infrastructure (QPI) as dependent variable. The results of the analysis highlight the influence of logistics performance indices on port infrastructure quality in Tunisia and Morocco. The results of the test the model using the partial least squares, confirm a significant influence of the identified factors on the quality of port infrastructure. It found show that it is vital to improve logistics performance, which contributes to improving the quali-ty of port infrastructure and increasing maritime trade; which promotes economic growth. Based on the results con-cerning the importance of port infrastructures, the quality of the latter is empirically examined. Our results show that Morocco tends to improve the quality of its infrastructure in order to improve its competitiveness. The originality of this research work consists in using the PLS (the partial least squares) regression method, which is contrary to previous studies, which have used other econometric methods in the same study field.